1992
DOI: 10.1038/clpt.1992.176
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose and steady-state pharmacokinetics and pharmacodynamics of oxycodone in patients with cancer

Abstract: The single-dose and steady-state pharmacokinetics and pharmacodynamics of oxycodone have been determined in patients with moderate to severe cancer pain. The mean +/- SD elimination half-life after single-dose administration of intravenous (4.6 mg to 9.1 mg) and oral (9.1 mg) oxycodone was 3.01 +/- 1.37 hours and 3.51 +/- 1.43 hours, respectively. After intravenous administration, the mean +/- SD volume of distribution was 211.9 +/- 186.6 L, and the mean +/- SD total plasma clearance was 48.6 +/- 26.5 L/hr. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 3 publications
6
67
1
1
Order By: Relevance
“…Plasma oxycodone concentrations were above the limit of detection (3 ng:ml) even at 0 h and with small daily doses, indicating a slower elimination of oxycodone, consistent with the longer elimination half-life (t 1:2) and better bioavailability of oral oxycodone compared with morphine reported in previous studies (12,22).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Plasma oxycodone concentrations were above the limit of detection (3 ng:ml) even at 0 h and with small daily doses, indicating a slower elimination of oxycodone, consistent with the longer elimination half-life (t 1:2) and better bioavailability of oral oxycodone compared with morphine reported in previous studies (12,22).…”
Section: Discussionsupporting
confidence: 61%
“…A wide individual variability in the plasma opioid concentrations was evident, as has been reported in previous studies (17,18,22). In cancer patients, no simple correlation between opioid and metabolite concentrations and pain relief has been found (19), although Faura et al (16) have reported a tendency towards greater stable phase morphine concentrations in cancer patients with optimal pain control.…”
Section: Discussionsupporting
confidence: 47%
“…Oxycodone clearance may also be considerably altered with changes in liver blood flow because of the high clearance of 46.8 l/h (ϭ780 ml/min), 16) and accordingly it is expected to decrease when hepatic blood flow is impaired. However, taking account of the high bioavailability of 60% 18) and 87%, 19) the oxycodone clearance, a metabolized amount of oxycodone, is overestimated and unlikely to be that large. Furthermore, changes in liver metabolic enzyme activity can have some effects on oxycodone clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Once peak plasma concentrations cation limit of oxycodone in plasma samples was are reached, oxycodone concentrations rapidly decline, 0.2 ng ml−1, with standard curve linearity between with an apparent terminal half-life ranging from 3.0 to 0.2 ng ml−1 and 100 ng ml−1. Inter-day and intra-day 5.7 h [ 5,7]. Because oxycodone is rapidly absorbed precision (expressed as per cent coefficient of variation) and quickly eliminated after oral administration, freranged from 0.4% to 9.9% for nominal standards quent dosing (every 4-6 h) is required to maintain ranging from 0.2 ng ml−1 to 100 ng ml−1.…”
Section: Introductionmentioning
confidence: 99%
“…The popuate-release oral solution is rapid and could be described lation mean pharmacokinetic parameters obtained by a simple first order absorption process with a lag describe the response in the typical (mean) individual. time: [ 5,7].…”
Section: Introductionmentioning
confidence: 99%